Brands and branding - Brown, Stephen, 1955 March 23- (Los Angeles ; London : SAGE, 2016)
This book introduces readers to the key components of brands and helps them to begin to make sense of them - what they are, what they do, why and how - using plenty of examples and references drawn from a wide range brands.
The rudiments of branding -- Brand names matter -- Logos, slogans, mascots, and more -- Brands tell stories -- Brands are living things -- Consumers beware -- Brand management -- Expanding the brand -- The brand stops here -- The dark side of the brand -- Pop goes the brand -- The brand finale.
Includes bibliographical references (pages 247-276) and index.
Keywords: Branding (Marketing); Brand name products; Brand name products